Effect of Nurses' Work Experiences in a COVID-19 Unit on Depression: Mediation Effect of Resilience and Moderated Mediation Effect of Organizational Trust - Doo, Eun-Young; Choi, Sujin (Frontiers in Public Health, 2022)
Aim Nurses work with a lack of organizational support and perceive an unsafe environment from their organizations, which has been related to depression. This study aimed to investigate the effect of nurses' work experiences in a COVID-19 unit on their depression, the mediation effect of resilience, and the moderated mediation effect of organizational trust. Methods Participants were 132 nurses working at a general hospital. Through questionnaires, data were collected during the COVID-19 pandemic and analyzed using SPSS 25.0 and SPSS PROCESS macro. Results Mean resilience was 2.15 ± 0.76; mean organizational trust was 3.03 ± 0.74; mean depression was 0.76 ± 0.63. 65.6% nurses with work experience in a COVID-19 unit had depression. Of the 27.2% nurses who showed moderate or higher levels of depression. Nurses' work experiences in a COVID-19 unit had a direct effect on depression and indirectly affected depression via resilience as a mediator. Resilience had a partial mediation effect, and organizational trust had a significant moderated mediation effect in the path from nurses' work experiences in a COVID-19 unit to depression mediated by resilience. Conclusions This study emphasizes the key role that healthcare organizations play in providing sufficient support to nursing staff to protect them from depression by improving nurses' resilience and organizational trust during the pandemic. Healthcare organizations need to develop a systematic structure to provide organizational support to nurses so that the organizational trust and resilience of nurses can be maximized.